Total Harmonic Distortion Comparison between Sinusoidal PWM Inverter and Multilevel Inverter in Solar Panel - Budiman, Firmansyah Nur; Ramadhani, Muhammad Ridho (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
This research compared the performance of PWM (Pulse Width Modulation) inverter and multilevel inverter in terms of their output voltage and current total harmonic distortion (THD). The inverters were designed to have the output voltage of 220 V at 50 Hz. The input voltage for both inverters are 400 VDC. For PWM inverter, the PWM technique utilized was sinusoidal PWM (SPWM) and for multilevel converter, the number of voltage level is five with diode-clamped topology. The study included circuit implementation, analysis, and THD calculation, all of which were carried out through simulation using PSpice software. In controlling the SPWM inverter output, the adjusted parameters included amplitude modulation ratio, frequency modulation ratio, and filter componentsâ parameters. On the other hand, the firing angles of the switching components were designated as controlling parameters in multilevel inverter. From the study, it was found that the best THD values of the designed SPWM inverter are 4.2% (voltage) and 1.7% (current), while those of multilevel inverter are 27% and 11%, for voltage and current, respectively. Thus, it can be concluded that SPWM inverter is better than 5-level inverter for the application in solar panel due to its lower THD. In our study, 5-level inverter did not satisfy the THD requirement specified in IEEE 512-1992, i.e. 5%.